2020
DOI: 10.1096/fj.202000732rr
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG6 promotes carcinogenesis by enhancing YBX1‐mediated translation of HIF1α in clear cell renal cell carcinoma

Abstract: Recent studies have showed that Small nucleolar RNA host genes (SNHGs) acted as a subset of long noncoding RNAs (lncRNAs) have critical roles in human cancer carcinogenesis. However, the biological functions of SNHGs in clear cell renal cell carcinoma (ccRCC) have not been fully investigated. In this study, we screened an oncogenic lncRNA termed SNHG6 using RNA-Seq data of ccRCC from The Cancer Genome Atlas (TCGA). Quantitative real-time PCR was then used to demonstrate the expression of SNHG6 in ccRCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…For example, SNHG26 has significantly upregulated in bladder urothelial carcinoma and associated with poor survival ( Bao et al, 2017 ). Overexpression of SNHG6 was found to promote cell proliferation and metastasis in clear cell renal cell carcinoma (ccRCC) by interacting with YBX1 ( Zhao et al, 2021 ). These existing experimental evidence further support the predicted TIILncSig in cancer carcinogenesis and progression and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNHG26 has significantly upregulated in bladder urothelial carcinoma and associated with poor survival ( Bao et al, 2017 ). Overexpression of SNHG6 was found to promote cell proliferation and metastasis in clear cell renal cell carcinoma (ccRCC) by interacting with YBX1 ( Zhao et al, 2021 ). These existing experimental evidence further support the predicted TIILncSig in cancer carcinogenesis and progression and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Y-box binding protein 1 (YBX1 or YB-1) is a transcription factor, expressed at various stages of development and in early hematopoiesis [269,270] , but is also active in tumor cells [271][272][273] . Deregulation of YBX-1 in carcinogenesis seems to be attributed to a combination of epigenetic alterations and MAPK signaling [274][275][276] . Furthermore, YBX1 binds to the promoter region of ABC transporters, including ABCB1, and predicts poor outcome (reviewed in [277] ).…”
Section: Ybx1mentioning
confidence: 99%
“…Numerous studies have shown that cancer progression is fostered by SNHG6 [ 170 , 171 , 172 , 173 ]. Moreover, SNHG6 can elevate the expression of HIF-1α by either sponging miRNAs or enhancing the translation of HIF-1α mRNA [ 150 , 151 , 152 ].…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%
“…Furthermore, the pro-tumorigenic effect of SNHG6 was also reported in clear cell renal cell carcinoma [ 152 ]. In a study concerning them, it was proposed that SNHG6 interacts with Y-box binding protein 1 ( YBX1 , also called YB1 ) and mediates the connection between YBX1 proteins and HIF-1α mRNAs to activate translation of HIF-1α transcripts [ 152 ] ( Figure 2 and Table 2 ).…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%